DEVELOPMENT AND EVALUATION OF MUCOADHESIVE NANOGEL OF NEVIRAPINE FOR VAGINAL APPLICATION - Rahman, Sheikh Sofiur; AHMED, ABDUL BAQUEE (International Journal of Applied Pharmaceutics, 2019)
Objectives: The main objective of this study was to develop and evaluate Nevirapine nanoparticle loaded mucoadhesive gel (NVP-Np mucoadhesive gel) for vaginal application for the treatment of HIV infection. Methods: NVP loaded nanoparticles were prepared by salting out method followed by incorporation in different gel bases to produce NVP-Np mucoadhesive gel The prepared gels were evaluated for their physicochemical parameters, rheological characteristics, mucoadhesion, in-vitro drug release and ex-vivo permeation of drug across porcine vaginal mucosa. Results: The result of FT-IR and DSC study confirmed the absence of incompatibility of NVP with excipients used in the formulations. The particle size of the prepared NVP-Np was found to be 243.8 ± 3.15 nm, a polydispersity index (PI) of 0.787± 0.002 and zeta potential value -17.12 mV, which revealed the stability of nanoparticles. All the formulations showed good homogeneity, spreadability, physical appearance and content uniformity. The pH of the mucoadhesive gel formulations was in the range of 3.70 ± 0.03 to 4.56 ± 0.02, which lies in the normal pH range of the vaginal fluid. The cumulative amounts permeated at 6 h were 832.23 ± 63.45 μg/cm2 , 592.13 ± 82.55 μg/cm2 and 941.32 ± 81.10 μg/cm2 from F1(1% Chitosan), F2(1% Carbopol 974P) and F3 (1% HPMC K100M ) respectively. A linear relationship [r2 > 0.9 (0.97 n 0.99)] was observed between the percentage cumulative amount permeated and time, indicating zero order kinetics. Conclusion: In conclusion, NVP-Np mucoadhesive gel was prepared successfully using salting out followed by a homogenization technique for vaginal application of NVP for the prophylaxis of HIV infection.